2011
DOI: 10.1186/1471-2458-11-s3-s17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balanced protein energy supplementation during pregnancy on birth outcomes

Abstract: BackgroundThe nutritional status of the mother prior to and during pregnancy plays a vital role in fetal growth and development, and maternal undernourishment may lead to adverse perinatal outcomes including intrauterine growth restriction (IUGR). Several macronutrient interventions had been proposed for adequate protein and energy supplementation during pregnancy. The objective of this paper was to review the effect of balanced protein energy supplementation during pregnancy on birth outcomes. This paper is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 25 publications
7
77
0
3
Order By: Relevance
“…5 In 2011, an estimated 165 million children aged ,5 years worldwide had stunted growth, with the majority residing in Asia and sub-Saharan Africa. 6 Prenatal multiple micronutrient (MMN) 7 and balanced energy and protein 8 supplementation result in a significant reduction in small-for-gestational age births (9% and 31%, respectively). However, the results of such interventions on postnatal growth yielded more dispersed results.…”
mentioning
confidence: 99%
“…5 In 2011, an estimated 165 million children aged ,5 years worldwide had stunted growth, with the majority residing in Asia and sub-Saharan Africa. 6 Prenatal multiple micronutrient (MMN) 7 and balanced energy and protein 8 supplementation result in a significant reduction in small-for-gestational age births (9% and 31%, respectively). However, the results of such interventions on postnatal growth yielded more dispersed results.…”
mentioning
confidence: 99%
“…Factors that have previously been found to contribute to intrauterine growth have included maternal nutrition (Belkacemi, Nelson, Desai, & Ross, 2010; Imdad & Bhutta, 2011) and placental development (Belkacemi et al, 2010), physical activity during pregnancy (Takito, Benicio, & Neri Lde, 2009), psychosocial stress (Littleton, Bye, Buck, & Amacker, 2010), and tobacco exposure (Suter, Abramovici, & Aagaard-Tillery, 2010), among others. Indeed, it appears that there may be complex relations between prenatal smoking exposure and the phenotypes of interest in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that focused on multiple micronutrients along with balanced energy and protein during pregnancy have even greater results on SGA [14, 32, 34]. Other trials have shown reduction in LBW by 20% with daily consumption of iron supplements and increases in birthweight with calcium supplementation in pregnant women [34]. …”
Section: Linear Growth From Preconception To Beyond the First 1000 Dmentioning
confidence: 99%